The Effort to Create Customer Engagement on Customer E_Banking (Empirical Studies on Bank BNI Regional Semarang) - Rivai, Alimuddin Rizal; Wahyudi, Wahyudi (JDM (Jurnal Dinamika Manajemen), 2016)
This study focused on testing the effect of variable customer value, support systems and knowledge of the customer's products to customer satisfaction and its impact on customer engagement. This study selects the object user's e-banking customers of Bank BNI Regional Semarang. The number of samples in this study of 100 respondents, using purposive sampling technique sampling. Processing data using SPSS version 16.0. Based on a statistical test using linear regression approach, then of seven hypothesis there are two hypotheses were rejected. The hypothesis is rejected is the influence of customer value on customer engagement, and support systems to customer engagement. While five other hypotheses, namely: the influence of the customer value, support systems, knowledge products to the satisfaction of the customer, as well as the effect of product knowledge and customer satisfaction on customer involvement is proven. Based on the results of this study, it can be concluded that to build customer engagement should be created customer satisfaction. While such satisfaction can be created through providing better customer value, the support system is up to date and easy, and provides knowledge products to customers continuously and thoroughly.